Single Nucleotide Polymorphisms in Pediatric Idiopathic Nephrotic Syndrome - Maija Suvanto; Timo Jahnukainen; Marjo Kestilä; Hannu Jalanko (International Journal of Nephrology)
Polymorphic variants in several molecules involved in the glomerular function and drug metabolism have been implicated in the pathophysiology of pediatric idiopathic nephrotic syndrome (INS), but the results remain inconsistent. We analyzed the association of eleven allelic variants in eight genes (angiopoietin-like 4 (ANGPTL4), glypican 5 (GPC5), interleukin-13 (IL-13), macrophage migration inhibitory factor (MIF), neural nitric oxide synthetase (nNOS), multidrug resistance-1 (MDR1), glucocorticoid-induced transcript-1 (GLCCI1), and nuclear receptor subfamily-3 (NR3C1)) in 100 INS patients followed up till adulthood. We genotyped variants using PCR and direct sequencing and evaluated estimated haplotypes of MDR1 variants. The analysis revealed few differences in SNP genotype frequencies between patients and controls, or in clinical parameters among the patients. Genotype distribution of MDR1 SNPs rs1236, rs2677, and rs3435 showed significant (p<0.05) association with different medication regimes (glucocorticoids only versus glucocorticoids plus additional immunosuppressives). Some marginal association was detected between ANGPTL4, GPC5, GLCCI1, and NR3C1 variants and different medication regimes, number of relapses, and age of onset. Conclusion. While MDR1 variant genotype distribution associated with different medication regimes, the other analyzed gene variants showed only little or marginal clinical relevance in INS.